Effect of special exercises according to the difficulty of the training unit on the physical abilities and the performance of 200m sprinters - Ali Sheerkhan, Lina; Rustum Yaqoob, Liza (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The purpose of this study was to identify the effect of special exercises according to the difficulty of the training unit on developing some physical abilities and on the achievement of a 200-meter run. The present study had a parallel group, experimental design. In the present study, 200m sprinters constituted the population and research community. The study was conducted in the clubs of the province of Baghdad. A total of 12 runners were recruited as the sample for the study by the intentional method. The participants were divided into experimental group and control group using odd even method. Considering the findings of this study, the researchers concluded that the adoption of special interval training exercises according to the difficulty of the training unit is useful to develop the physical abilities and the performance of 200m sprinters.